2016
DOI: 10.4187/respcare.04127
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Aerosol Delivery in Simulated Spontaneously Breathing Patients With Tracheostomy Using Different Humidification Systems With or Without Exhaled Humidity

Abstract: BACKGROUND: Aerosol and humidification therapy are used in long-term airway management of critically ill patients with a tracheostomy. The purpose of this study was to determine delivery efficiency of jet and mesh nebulizers combined with different humidification systems in a model of a spontaneously breathing tracheotomized adult with or without exhaled heated humidity. METHODS: An in vitro model was constructed to simulate a spontaneously breathing adult (tidal volume, 400 mL; breathing frequency, 20 breaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 11 publications
0
27
3
Order By: Relevance
“…Although the humidity change results were far different from most of the previously published in vitro studies, which recommend switching off the humidifier when delivering aerosol to ventilated patients, 9,19,20,[42][43][44][45] the results were very close to our previous findings of the effects of humidity change on aerosol delivery in auto-CPAP ventilated subjects 16 and invasively ventilated subjects. 21,22 This finding shows that there is no need to discomfort the patient by switching off the humidifier for aerosol delivery because the dry gas could potentially be harmful to the lung and the increase in delivered aerosol was insignificant.…”
Section: Discussioncontrasting
confidence: 52%
“…Although the humidity change results were far different from most of the previously published in vitro studies, which recommend switching off the humidifier when delivering aerosol to ventilated patients, 9,19,20,[42][43][44][45] the results were very close to our previous findings of the effects of humidity change on aerosol delivery in auto-CPAP ventilated subjects 16 and invasively ventilated subjects. 21,22 This finding shows that there is no need to discomfort the patient by switching off the humidifier for aerosol delivery because the dry gas could potentially be harmful to the lung and the increase in delivered aerosol was insignificant.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous in-vitro studies recommended switching off the humidifi er for better delivery [8][9][10][11]. However, our results showed that the humidity had much less effect on aerosol delivery during Auto-CPAP NIV and those in-vitro studies over estimate the effect of humidity on aerosol delivery.…”
Section: Discussioncontrasting
confidence: 54%
“…Most studies of humidifi cation effects on aerosol delivery were in-vitro and all of them recommend switching off the humidifi er while delivering aerosol to NIV patients for better delivery [5][6][7][8][9][10][11]. However, the undesirable effect of inhaled dry gas, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosol delivery in non-invasive ventilation (NIV) was proven to be of benefit and has been well studied [5,[7][8][9][10][11]. However, the effect of the change of design of nebulizers with the same mechanism on delivery has not been studied much.…”
Section: Introductionmentioning
confidence: 99%